Large Cysticercus in the Cerebellopontine Angle: Case Report - Sushil Kumar; Amit Garg; Amit Handa (Indian Journal of Neurosurgery)
Neurocysticercosis is an infection of the central nervous system caused by larvae of the pork tapeworm Taenia solium. We report a case of large cyst in the cerebellopontine angle that increased in size under observation and surgery revealed it to be cysticercus. It was removed in toto and patient improved on follow-up.